PENGARUH TAX AVOIDANCE DAN LAINNYA TERHADAP NILAI PERUSAHAAN NONKEUANGAN DI BURSA EFEK INDONESIA - Vivi Ferencia Tantono; Umar Issa Zubaidi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
Abstract: This study aims to examine and analyze the effect of tax avoidance, return on assets, current ratio, debt to equity ratio, institutional ownership, dividend policy and company size on the nonfinancial firm value listed on the Indonesia Stock Exchange. This study used 90 non-financial companies listed on the Indonesia Stock Exchange and were selected using the purposive sampling method during 2019-2021. This hypothesis testing uses a multiple regression model as a data analysis method. The results of this study explain that return on assets and debt to equity ratio have an influence on firm value, while tax avoidance, current ratio, institutional ownership, dividend policy, and firm size have no effect on firm value.